APLIKASI SIFAT ANTIOKSIDAN EKSTRAK TANAMAN TURI TERHADAP BIOLISTRIK SEBAGAI PENUNJANG REGENERASI KULIT - Reqgi First Trasia; Farahdhiya Millati Hawa; Haura Firlanti Putri; Samuel Nicolas Agustinus Panjaitan; Aslam Aryatama (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
The skin has a great risk of various diseases due to exposure to the external environment. Skin cell activity – including regeneration, can be observed through electricity – or what can also be called skin cell bioelectricity. In dealing with the skin problems mentioned previously, using skin care products that contain active ingredients that can fight free radicals and stimulate skin cell regeneration is very important. Antioxidants are one of the active ingredients needed in skin care products. When free radicals attack skin cells, antioxidants act to accept electrons from damaged molecules, thereby forming new molecules that are more stable and non-damaging. With its properties that are able to inhibit the oxidation process, antioxidants are the key to maintaining the health and beauty of the skin and preventing obstruction of the skin cell regeneration process due to free radicals. Apart from that, antioxidants also have anti-inflammatory properties which can help reduce inflammation of the skin such as acne, dermatitis, or rosacea which causes damage to skin cells. One plant that is rich in antioxidants is the turi plant (Sesbania grandiflora). This research aims to investigate the antioxidant effect of mature turi plant extract on skin bioelectricity as a support for skin cell regeneration. It is hoped that this research will later become a reference for innovative development of atopic treatment using turi plant extract as the main ingredient.